CLASSIFICATION OF RUSSIAN REGIONS ON THE DYNAMICS OF DEVELOPMENT IN THE YEARS 2005-2011 - I. A. Vinyukov; Yu. N. Blagoveschensky; L. P. Konnova; E. V. Maevskiy; P. V. Yagodovsky (Финансы: теория и практика)
The article is devoted to the development of classification of the subordinate entities of the Russian Federation based on the data of the State statistical reporting for 2005-2011 and aimed at assessment of financial solvency of regions concerning budget backing, attracting of investments, promoting export-import relationship between foreign countries and their fiscal policy in the relations with the federal center. The main achievement is a new approach to formation of integrated characteristics (indexes) which work equally well during different periods of development of the economy (range 2005-2011 contains upswing, crisis and an initial stage of its surmounting). As a result 4 indexes reflecting separate sides of affluence of regions were designed, and common criteria of classification were created on their base. As a result all the regions were divided into 6 well interpreted classes. Shows non-conditionality the classification by regressions on indicators of well-being and evaluated regression of recent on financial indicators.